Mobile radio systems applications in electric/gas utilities. II (IEEE transactions on power delivery, 1991)
As part of an effort to provide a service to the electric/gas utility industry, a survey of over 32 large electric/gas Canadian and US utilities was conducted in January 1988 to determine the status and value of existing mobile radio applications along with plans for future replacement or upgrading. Part II of the report on this subject include: (a) mobile radio system replacement considerations; (b) sources for the latest equipment and systems information; (c) descriptions of state-of-the-art new mobile radio microprocessor-based trunking technology, available from manufacturers; and (d) typical applications involving replacement of only the control system for a bulk transmission utility and replacement of an entire mobile radio system for a transmission and distribution utility.< >